Legal Responsibility Of The Board Of Directors In A Limited Liability Company For Company Losses - I Kadek Alam Kusuma Putra (jurnal.unprimdn.ac.id, 2025)
Limited Liability Companies are business entities that play a significant role in Indonesia's economic activities, characterized by democratic principles and the separation of shareholder rights and obligations. This article examines the application of the fiduciary duty principle to the responsibilities of directors, particularly regarding the prevention and management of corporate losses, as well as the legal basis for the implementation of derivative suits by shareholders in Indonesia. Fiduciary duty requires directors to act in good faith, prudence, and loyalty, with the business judgment rule mechanism protecting personal liability. Derivative suits serve as a legal instrument for shareholders to hold directors accountable, although procedural regulations in Indonesia are still limited and minimum share ownership requirements are considered to hinder access to justice for minorities. Case studies of court decisions demonstrate important developments related to the protection of minority shareholders. This study recommends improving legal education for directors, improving derivative suit regulations, strengthening internal oversight functions, and implementing Good Corporate Governance principles to maintain corporate integrity and sustainability.